EnviSAT ASAR microwave imaging for earth mapping - Wang, Zhi. (2013)
This report would provide a tutorial introduction to Interferometric Synthetic Aperture Radar (InSAR) remote sensing technique. Basic principles and applications are summarized firstly to give a fundamental understanding to the InSAR.